SYIAR ISLAM DI PLATFORM SHORT VIDEO: (ANALISIS SEMIOTIK PESAN DAKWAH QUR’ANI) - Deni Rahman (STAI DI AL-HIKMAH, 2025)
This study discusses the phenomenon of Islamic da'wah on short video platforms such as TikTok which is now a new space for the dissemination of Quranic da'wah messages among Generation Z. The main problem lies in how the meaning and symbols of da'wah messages are constructed and reinterpreted by the digital generation. The purpose of this study is to analyze the signs and meanings of the Quranic da'wah message through Roland Barthes' semiotic approach, focusing on denotative, connotative, and mythological aspects in digital da'wah content. This study uses a literature method by collecting data from relevant academic literature, journals, and previous research. The results of the study show that digital da'wah is transformed into a new sign system that combines spiritual values with visual aesthetics, making the Quranic message more communicative for Generation Z. In conclusion, Islamic teachings in digital media reflect the adaptation of da'wah to modern visual culture without losing the substance of Quranic values.